Diary of a fairy godmother [compact disc, unabridged] - Codell, Esmé Raji, 1968- (Listening Library, 2005)
When her training as a wicked witch doesn't go so well and she is expelled from charm school, Hunky Dory decides to follow her real passion of becoming a fairy godmother where she will use her magic to help others fulfill their romantic dreams.